Do pre‐existing microcracks play a role in the fracture resistance of roots in a laboratory setting?. (24th September 2020) - Cavalcante, D. M.; Belladonna, F. G.; Simões‐Carvalho, M.; Carvalhal, J. C. A.; Souza, E. M.; Lopes, R. T.; Silva, E. J. N. L.; Dummer, P. M. H.; De‐Deus, G.
Abstract: Aim: To investigate a potential cause–effect relationship between dentinal microcracks and fracture resistance of mandibular incisors that had not been endodontically treated. Methodology: Sixty mandibular incisors with circular‐shaped canals were selected based on micro‐computed tomographic scans to create a homogeneous sample. The cross‐sectional images of the specimens were screened to identify and quantify the presence of dentinal microcracks. Then, teeth were embedded in polystyrene resin and subjected to axial compressive loading using a universal testing machine. After fracture, the roots were re‐scanned and fractography analysis was performed by inspection of 3D models to verify crack propagation. Spearman's rank correlation was used to assess the correlation between the number of microcracks and force required to fracture. Results: Dentinal microcracks were detected in 79% of the specimens ( n  = 44). The incidence of microcracks varied between teeth from 6% to 42% of the total slices per sample (average of 14 ± 17%). The number of microcracks per sample varied from 0 to 1605, with an average of 412 ± 484 (median = 221 and IQR 25% = 15/75% = 658). The load at failure values varied from 227 to 924 N, with an average of 560.3 ± 168.1 N (median = 561 and IQR 25% = 458/75% = 694). The Spearman correlation coefficient (rho) equalled 0.065. Conclusions: There was no cause–effect relationship between the number of dentinal microcracks and the fracture resistance of nonendodontically treated mandibular incisors. The presence and quantity of microcracks did not make these roots more prone to fracture.